Combating Climate Changes Through Fiscal Policies in Developed World: Key Insights for Indonesia from Scandinavian Green Tax Scheme - Nurulita, Ainaya Fatimah; Prasidya, Tusta Citta Ihtisan Tri (Yayasan Ilomata, 2025)
Climate change remains a pressing global issue, necessitating innovative fiscal policies to mitigate its impact. Green taxation, first conceptualized by Pigou in the 20th century, has emerged as a pivotal tool in encouraging sustainable practices while penalizing environmental degradation. This study examines the implementation of green tax policies in Denmark, Norway, and Sweden, highlighting their success in reducing emissions and fostering renewable energy adoption. Drawing lessons from these Scandinavian models, the research explores how Indonesia can tailor similar strategies to strengthen its green taxation framework. By adopting a comparative case study approach, this paper identifies critical success factors, including gradual implementation, public acceptance, and balancing economic and environmental goals. The findings aim to inform Indonesia's policymaking, enabling the alignment of fiscal policies with sustainable development objectives.